Pengaruh Pemberian Pupuk Organik Cair Molase Terhadap Pertumbuhan Vegetatif Tanaman Cabai Merah (Capsicum annuum L.) - Angga Theo Fanny; Widya Lestari; Badrul Ainy Dalimunthe (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2022)
This study aims to obtain the right combination of POC Molasses and PGPR doses to increase the vegetative growth of red chili plants. The research was conducted in dusun IV, Desa Sidorukun, Kec. Pangkatan, Kab.Labuhanbatu. The research time starts from April to June 2021 until it is finished. The research method used was (RAK) Randomized Block Design, 1 factor, 3 levels, 9 combinations with 3 replications to obtain a total of 27 polybag units. The data obtained were analyzed using the F test at the 5% level, if significantly different, further tests were carried out using the Tukey test at the 5% level. The results of the ANOVA test at the 5% level showed that the administration of POC Molasses affected several parameters observed in the M2 sample, such as the number of leaves as many as 160.67 leaves, the number of branches as many as 85.00 stalks and plant height 61.67 cm, with different doses determined. after 6 MST. It can be concluded that the POC Molasses had no significant effect on the M0 treatment, which took longer to grow but in the M1 and M2 treatments, the growth was better. Giving POC Molasses had no significant effect on all observation parameters, especially on the number of leaves. So there is no further test after that. Keywords: POC molasses, PGPR, red chili